Step-by-step explanation:
which system explain more please
If c = 8 and d = -5:
a) c - 3 = 8 - 3
= 5
b) 15 - c = 15 - 8
= 7
c) 3(c + d) = 3(8 + (-5))
= 3*3
= 9
d) 2c - 4d = 2(8) - 4(-5)
= 16 + 20
= 36
e) d - c^2 = -5 - (8)^2
= -5 - 64
= -69
f) 2d^2 + 5d = 2(-5)^2 + 5(-5)
= 50 - 25
= 25
Answer:
i think he is correct
Step-by-step explanation:
Let x=number 1 let y=number2
there sum is equal to 70
then
number1+number2=70
substituting
x+y=70
y=70-x
let there product will be p
p=xy
substituting
p=x(70-x)
which is choice c